Enhancing Youth Cricket Performance: Insights From Field-Based Assessments of Strength, Endurance, and Agility - Basavaraj Motimath; Mansoor Pasha A (Journal of Coaching and Sports Science, 2025)
Background The physical demands of cricket, particularly in youth players, encompass critical components of strength, endurance, and agility, which are essential for optimal performance and maintaining competitive success. Strength, endurance, and agility are vital in enhancing youth cricketers' overall physical fitness and performance levels, directly influencing their ability to sustain high-intensity efforts, execute precise movements, and recover effectively during matches and training sessions. Aims: This research aimed to evaluate the field-based performance levels of young cricketers in Belagavi through innovative assessments: the wall squat, 2km time trial, and Run-a-three tests, highlighting their importance in enhancing player fitness and performance.Methods: A cohort of 100 young cricketers (aged 18-24) with a minimum of 2 years experience underwent comprehensive assessments using the wall squat, 2km time trial, and Run-a-three tests across various cricket grounds in Belagavi. Statistical analyses provided insights into their fitness levels across different player categories (batsmen, bowlers, all-rounders, and wicketkeepers).Results: Significant variations in fitness levels were observed among player categories, with wall squat endurance being the most notable area for improvement, as the mean performance was 51.54 ± 20.79 seconds. The average 2km trial was completed in 10.03 ± 1.42 minutes, while the Run-a-three drill averaged 11.86 ± 1.33 seconds. These findings highlight the critical need for targeted fitness interventions to enhance lower body endurance across all roles.Conclusion: This study underscores the imperative for tailored fitness regimens to address deficiencies in strength, endurance, and agility among young cricketers in Belagavi. These targeted interventions can enhance their competitive readiness and support long-term athletic development. Future research should explore the specific impact of these fitness interventions on performance metrics and injury prevention, providing further insights into optimizing youth cricket training programs.